A METODOLOGIA WEBQUEST COMO ESTRATÉGIA DE ENSINO MOTIVADORA DA APRENDIZAGEM DA LEITURA E DA ESCRITA NO 5º ANO DO ENSINO FUNDAMENTAL - MENDES , Débora Suzane Gomes (2018)
The present research refers to the analysis of the WebQuest Methodology in the teaching and learning process of reading and writing in Basic Education. Thus, the general purpose of this study is to investigate the efficacy of the WebQuest Methodology in the teaching and learning process of reading and writing, specifically with students of the 5th grade of a public school in São Luís – MA. The research also presents specific objectives: a) to verify students and teachers’ interests, motivations and difficulties related to the use of ICT in education; b) to develop a WQ in benefits of the teaching and learning practices of reading and writing for the 5th year of elementary school; d) to evaluate the contributions of the tasks proposed in WebQuest produced as motivating strategies in the teaching and learning process of reading and writing. In order to reach these objectives, we took a cyclical and methodological route based on the research method of Research-Strategic Action, with a qualitative approach, predominantly. The instruments and data collection techniques used in this research were: non-participant observation, participant observation, preliminary questionnaire, individual self-assessment questionnaire, group self-assessment questionnaire and focus group interview. The subjects participating in the research consist of a Portuguese teacher, a Computer Science teacher and sixty-six students from 3 classes of the fifth year of elementary school at the School of Application of the Federal University of Maranhão (COLUN/UFMA). The obtained results allow us to conclude that the WebQuest Methodology is a potential educational strategy, because it motivates the process of reading and writing through internet browsing and the resolution of challenging activities that stimulate abilities construction of the superior cognitive domain, such as analyzing, evaluating, creating, as well as, the skills of the 21st century and the formation of an active, autonomous, cognitive and active reader/writer in his/her reading and writing learning process.